2019
DOI: 10.20429/ger.2019.160104
|View full text |Cite
|
Sign up to set email alerts
|

Student Involvement In IEPs

Abstract: There has been a recent initiative for students to be involved in their Individualized Education Plan. The goal is for students to become self-advocates and learn to develop goals that pertain to their interests. The study examined this process of including students by addressing three questions. First, does student involvement in their IEP lead to greater mastery of IEP goals? Second, does student involvement in their IEP impact academic achievement? Third, in what ways does the Self-Advocacy Strategy, IPLAN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Applying IEP for children with disabilities helps them understand, develop, write, and participate in their IEP committee and develop Self-Advocacy skills (Pounds & Cuevas, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Applying IEP for children with disabilities helps them understand, develop, write, and participate in their IEP committee and develop Self-Advocacy skills (Pounds & Cuevas, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are also many researchers who have sought to improve reading outcomes for K-12 students (Cuevas, et al, 2014, Cuevas, et al 2012, with some focusing specifically on reading development for elementary-level students (Tankersley & Cuevas, 2019;Zavala & Cuevas, 2019). Still other studies have concentrated on bridging the learning gap for young students with special needs (Hendy & Cuevas, 2020;Hughes & Cuevas, 2020;Pounds & Cuevas;. It could be argued that the present study addresses a crucial area of education by distilling its focus down to addressing the reading ability of elementary-aged children with special needs.…”
Section: Implications and Future Researchmentioning
confidence: 91%
“…Although IDEA (2004) is somewhat vague regarding the exact role of the student during the IEP process, students may be included to participate in IEP meetings. IEP participation has been linked to positive outcomes among students, such as increased knowledge about their disability (Mason, McGahee-Kovac and Johnson et al, 2002;Nolan-Spohn, 2016), increased self-determination skills (Wehmeyer, 2005) and positive academic outcomes (Barnard-Brak and Lechtenberger, 2010). Educators have reported that students who lead their IEP meetings have a better understanding of their personal strengths and limitations and have greater knowledge of their rights and the resources that are available to them (Mason et al, 2004).…”
Section: Introductionmentioning
confidence: 99%